Literatur Review : Pengaruh Senam Hamil Terhadap Kualitas Tidur Ibu Hamil Trimester III: Literature Review : the Effect of Pregnant Exercise on the Sleep Quality for Pregnant Women in the Third Trimester - Desrinah Harahap; Yuni Yulia; Fauziah H Wada (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Pregnancy exercise is an important method to maintain or improve the physical balance of pregnant women and is an exercise therapy given to pregnant women in the third trimester to achieve a fast, easy and safe delivery. Aim: This literature review is to explain non-pharmacological therapy to determine the sleep quality of third-trimester pregnant women. Method: A literature review using the Literature search method on Google Scholar Results: with the keywords